ASY-SYATIBI DAN KONSEP ISTIQRAâ MAâNAWI (Sebuah upaya Pengembangan Hukum Islam) - Fahimul Fuad, Moh (AS-SALAM, 2012)
Basically, Islamic law is the law of all things, human and divine. It meansthat the source of Islamic law, actually, comes from the devine of God, andâin other hand- the creation of human being through his reason. But, afterfalling of Islamic civilization, Islamic law becomes marginal law that justhas been aplicated for a part of human life aspect, for example family law.Further, Islamic law becomes weak, because of his inability to answermodern problems. Thus, it needs an empowerment.Many of experts assume that for Islamic law empowerment, the mostimportant to be improved is methodological aspect, that is Islamic legaltheory called as ushul fikih. It needs improving in order to be able to guidethe development of social change from the law perspective. What has beengiven by the former ushuliyyun, especially four Islamic law schools, in theform of methodological Islamic law isnât enough to cover the problems oflaw. Then, Asy-Syatibi came and offered the new method of Islamic legaltheory. His method offers the new perspective in understanding the sourcesof Islamic law. It is, comonly,called as istiqraâ maânawi. This paper willdescribe and explain about it.Keywords: Hukum Islam, Asy Syatibi, Istiqraâ Maânawi